Transnational Social Protection: Migrants' Strategies and Patterns of Inequalities. Issue 3 (8th November 2014) - Faist, Thomas; Bilecen, Başak; Barglowski, Karolina; Sienkiewicz, Joanna Jadwiga
Abstract How migrants organise their social protection is not a straightforward process but, rather, a much more intricate and nuanced one, which takes into account the manifold state regulations, supranational frameworks and civil society organisations, as well as the migrants themselves and their significant others spread across various state borders. This introduction to our special issue examines the social protection strategies of migrants, the ways in which transnationality shapes the access and use of informal social protection, and their implications for migrants' life chances and thus the production of social inequalities. It provides a context for understanding the articles that follow in this special issue as statements of current research on welfare and migration, as challenges of concern in transnational studies and as examples of migrants' social protection, influenced by a variety of heterogeneities which intersect with transnationality. Copyright © 2014 John Wiley & Sons, Ltd.